Manajemen Risiko Pada Skema Kpbu Preservasi Jalan Nasional Lintas Timur Sumatera Di Provinsi Sumatera Selatan - Said, Balqis Fataya; Mahani, Iris; Puri, Eliza Rosmaya; Gayatri K. P. , Rani (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The Indonesian government has accelerated infrastructure development as reflected in the RPJMN 2015-2019 and one of them is road infrastructure, namely Lintas Timur Sumatera National Road in South Sumatra Province (Jalintim Sumsel). Existing condition data shows that Jalintim Sumsel needs to do road preservation. There is a gap between the availability of government funds (APBN) and infrastructure needs listed in the RPJMN 2015-2019, financing for road preservation at Jalintim Sumsel can be carried out using other financing alternatives, namely the Public Private Partnership (PPP) scheme with availability payment. In the PPP scheme, it is necessary to carry out risk management so that risks that are difficult to fulfill can be estimated how to mitigate them, one of which is by risk allocation. The research objective is to find out what risks occur in the project, the dominant risk prediction, and the dominant risk allocation. The scope of risk management is carried out on two perceptions of the parties involved in the project, namely BUP and PJPK with a long list of risks and probability (P) and impact (I) assessment questionnaire, and also risk cost assessment through interviews. The results of the analysis show that there are 63 risks faced by the PJPK and 60 risks faced by the BUP, there are 7 dominant risks according to the PJPK's perception and 4 dominant risks according to the BUP's perception. The results of risk allocation show that for the Risk of Increase in Construction Costs, Poor Contractor/Subcontractor Performance, Increase in O&M Costs (overloading), Inflation Rate, and Interest Rate are more allocated to BUP. As for the Risk of Failure to Pay AP on Time allocated to PJPK, as well as for Politics Force Majeure Risk and Prolonged Force Majeure are allocated jointly.